Current and novel therapeutic strategies in celiac disease. Issue 9 (1st September 2016) - Kurada, Satya; Yadav, Abhijeet; Leffler, Daniel A.
ABSTRACT: Introduction : A gluten free diet (GFD) is the only available treatment for celiac disease (CD). However many patients fail to respond fully clinically or histologically. Several surveys highlight the psychosocial implications of adherence to a GFD. Hence, efforts are ongoing to develop therapeutic strategies beyond a GFD. Areas covered : We conducted a search of PubMed and clinicaltrials.gov to extract articles on CD using keywords including 'celiac disease' and 'refractory celiac disease' (RCD) and focused on articles conducting pathophysiologic and therapeutic research in/ex-vivo models and human trials. We highlight novel therapeutics that manipulate these mechanisms including tight junction regulators, glutenases, gluten sequestrants and immunotherapy using vaccines, nanoparticles that may serve as adjuncts to a GFD or more ambitiously to allow for gluten consumption. We also highlight the role of anti-inflammatories, immunosuppressants and monoclonal antibodies in RCD. Expert commentary : Therapeutics including tight junction regulators, glutenases have the potential to be approved for non-responsive CD or as gluten adjuncts. We expect results of various phase 1/2 trials using AMG 714, BL 7010, IgY antibodies to be published. In the interim, off-label use of 5 amino-salicylates, budesonide, nucleoside analogues and newer biologics developed for other inflammatory diseases will be used in RCD.